2021
DOI: 10.1038/s41590-020-00847-4
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cells suppress Plasmodium falciparum blood-stage infection by direct killing and phagocytosis

Abstract: Activated Vγδ9Vδ2 (γδ2) T lymphocytes that sense parasite-produced phosphoantigens are expanded in Plasmodium falciparum -infected patients. Although previous studies suggested that γδ2 T cells help control erythrocytic malaria, whether γδ2 T cells recognize infected red blood cells (iRBCs) was uncertain. Here we show that iRBCs stained for the phosphoantigen sensor, butyrophilin 3A1 (BTN3A1). γδ2 T cells formed immune synapses and lysed iRBCs in a contact, phosphoantigen, BTN3A1 and deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 53 publications
10
52
1
Order By: Relevance
“…In agreement with previous reports, we observed expanding γδ T cells after the initial inflammatory response in response to the infection (45,46). gd T cells are suggested to have an important role in the control of malaria (29) and direct anti-parasite functions during the blood stage have been reported (24). In this study, we observed that the acute phase inflammatory response was positively associated with expansion of Vd2 + gd T cells, and further that this was strongly impacted by previous malaria exposure, resulting in a dampened inflammatory response and less gd T cell expansion.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In agreement with previous reports, we observed expanding γδ T cells after the initial inflammatory response in response to the infection (45,46). gd T cells are suggested to have an important role in the control of malaria (29) and direct anti-parasite functions during the blood stage have been reported (24). In this study, we observed that the acute phase inflammatory response was positively associated with expansion of Vd2 + gd T cells, and further that this was strongly impacted by previous malaria exposure, resulting in a dampened inflammatory response and less gd T cell expansion.…”
Section: Discussionsupporting
confidence: 57%
“…Vd2 + gd T cells are known to activate and expand during a primary P. falciparum infection in response to malaria phosphoantigens and that their activity is modulated upon subsequent infections (47). Given the recently described role of Vd2 + gd T cells in antiparasitic activities via antibody-CD16 dependent phagocytosis of infected erythrocytes and cytotoxicity (24,25), associations to possible activity modulating factors are of interest. The benefit of reduced expansion of gd T cells due to a dampened inflammatory response could be to reduce overall inflammatory responses, which are otherwise potentially detrimental to the host (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to prevent malaria-associated morbidity and mortality tight control of parasitemia is essential. We previously demonstrated, and it was very recently independently confirmed (54), that the lymphocyte subset bearing the gd T cell receptor contributes critically to the inhibition of parasite growth in the blood phase. The inhibition of late stage parasite depended on the expression of GNLY and GzmB but was independent of PFN.…”
Section: Discussionmentioning
confidence: 72%
“…The important role γδ T cells play (including Vγ9Vδ2 + T cells) in immune responses to infections in humans has been well established [5][6][7][8][9][10]. Because of their characterized cytotoxic potential against a variety of tumor cells in vitro [11,12] and in vivo in mouse models [13][14][15], they are widely investigated for their putative roles in cancer immunity and therapy (Box 1).…”
Section: Using Innate Immune Mechanisms To Target Cancermentioning
confidence: 99%